PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BATIK JAMBI DI MUARA BULIAN (STUDI KASUS KONSUMEN BATIK JAMBI MARYANA MUARA BULIAN) - Dini Haryati (Jotika Journal In Management and Entrepreneurship, 2023)
This study aims to determine the effect of product quality and price on purchasing decisions of Jambi batik (Case Study of Jambi Batik Maryana Muara Bulian). The population of this research is all consumers of Jambi Maryana batik. The results of this study indicate that product quality has a significant effect on purchasing decisions with the results obtained tcount>ttable (2,884 > 1,666). This shows that H0 is rejected and H1 is accepted. Prices have a significant effect on tcount>ttable (7,765 > 1,666). This shows that H0 is rejected and H1 is accepted. This partially there is an influence between product quality and price on purchasing decisions. By looking at the results of the coefficient of determination (r square) of 0.606 which means the magnitude of the role or contribution of product quality and price variables that can increase purchasing decisions by 60.6% and 0.394 or 39.4 is a residual variable that has not been studied in research this.